Mapping students' listening problems and strategies - Risa Arroyyani (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2021)
Listening is crucial to understand spoken language and to support the other language skills mastery; however, some students find several problems related to listening. This study aims to determine students’ listening problems and listening strategies they apply to overcome the difficulties. The research type is qualitative research using questionnaires and interviews as research instruments. This research used descriptive statistics to analyze the data obtained from the questionnaires and an interpretation of coding to analyze the interview transcript data. The respondents were 31 pharmacy students involved in the English for Pharmacy class, and there were three of them engaged in a structured interview session. The findings of this study were: (1) the students were moderate-level in listening problems of perception (M=2.91), parsing (M=3.18), and utilization (M=2.95) phase, (2) the students were high-level strategy users in cognitive, meta-cognitive, and socio-affective strategy, (3) the students mostly experienced difficulty in the parsing phase compared to two other problems and applied cognitive and meta-cognitive strategies than socio-affective strategy.